Ensifentrine: A Potential Shift in COPD Management - Cheema, Zian Zafar; Muhammad Daniyal,; Muhammad Ibrahim Arif, (Journal of the Pakistan Medical Association, 2025)
Ma’am, Chronic Obstructive Pulmonary Disease (COPD) is a progressive condition caused by damage to the airways and other parts of the lungs, predominantly affecting the smoking population. Over the years, treatment of COPD has evolved significantly based on advancingresearch. Currently, a triple therapy regimen that combines a Long-Acting Beta Agonist (LABA), a Long-Acting Muscarinic Antagonist (LAMA), and an Inhaled Corticosteroid (ICS), is the standard of care for COPD management (1). However, the recent FDA approval of Ensifentrine in June 2024 offers a promising new approach to the treatment of this chronic disorder. Ensifentrine is a novel inhaled phosphodiesterase 3 and 4 inhibitor with both bronchodilatory and anti-inflammatory properties (2). The recently conducted ENHANCE trials have validated its efficacy, demonstrating significant improvements in lung function and a reduction in COPD exacerbations among patients using the drug (2). Moreover, its safety profile has been deemed comparable to that of placebo, as reported in the same trials. In contrast, its oral counterpart, roflumilast—a PDE4 inhibitor introduced in 2011—failed to live up to its potential in clinical practice due to severe adverse effects. Nonetheless, ensifentrine seems to avoid the same fate. Given the promising safety profile Ensifentrine warrants consideration as a viable treatment option, particularly in comparison to regimens involving inhaled corticosteroids. Especially given that Ensifentrine exhibits promising anti-inflammatory effects, while long-term use of corticosteroids can be challenging due to side effects such as dysphonia, oropharyngeal candidiasis, adrenal suppression, cataract formation, and psychiatric disturbances (3). This revelation of Ensifentrine holds a promising potential, though many important questions remain unanswered. Notably, it remains to be seen whether Ensifentrine is most effective as a monotherapy or as part of a combination therapy with other bronchodilators, although preliminary data suggest that the latter may offer superior outcomes (4). Additionally, a comprehensive study exploring its anti-inflammatory effects would be valuable, as Ensifentrine could offer a potential alternative to corticosteroids. The availability and pricing of the drug remain relevant concerns at present. While the answers to these questions will become clear over time, Ensifentrine continues to be hailed as a significant breakthrough in COPD treatment—and rightly so.